Mental Well-Being, Challenges, and Coping of College Students Amid the COVID-19 Pandemic - Castillo, Sheryll Ann M. (8ISC Abstract Proceedings, 2022)
The global COVID-19 pandemic has massively impacted all areas of human existence, which has forced several sectors in society to modify their processes and protocols. The education sector had to use the online platform in the delivery of its teaching-learning services – a modality for which teachers and students alike were unprepared for. Since much is still to be improved in the delivery of teaching using the online platform, this study employed a descriptive survey design to identify the challenges college students experience during this pandemic and what they do to cope with these challenges. A total of 338 college students from a university in Cavite, Philippines, responded to a mixed-design online survey composed of the 14-item Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) to measure students’ mental well-being and open-ended questions that asked in detail challenges that students experience and coping activities that they do to cope with the challenges. The WEMWBS resulted in a sum average mean of M= 45.89 from a possible total mean of 70, which indicated a moderate level of mental well-being. The qualitative responses generated four themes in terms of challenges that depict issues in online learning, family, health, and environment. The challenges in these areas greatly affected students’ mental health, which manifested changes in their cognition, effects, and behavior. In terms of coping, 40% of the respondents used religious beliefs and practices (prayer, trusting God), 23% of the students found support from family and friends to be comforting, 10% indicated that a change in mindset and attitude was effective, while 4% had to resort to learning a new hobby. Fifteen percent of the students used a combination of all these coping activities, while 8% admitted that they do not know how to cope at all. These results imply that schools should not solely focus on the implementation of online teaching, but such delivery must ensure that even students’ emotional and mental health needs are met. Recommendations for the school’s academic and non-academic areas are further discussed in the study. Keywords : online learning, covid-19 pandemic, students’ mental health